MENELUSURI SEJARAH & KARYA SENI JAKARTA BIENNALE - Farid Abdullah (Universitas Trisakti, 2009)
AbstractHistorically and culturally , Southeast Asia is a place where great civilizations and ancient, influential religions meet , throught trades, migration, and colonization. History of art form in Southeast Asia is a part of the cultural life in our daily activities, the organizing of such events as The Jakarta Biennale, has therefore been called for and it simultaneously shows Jakarta's sparkle in the process of art and cultural development. There are two main differences between the history Jakarta Biennale before and today. First, that the Jakarta Biennale today is international nature. Second, it is held in conjuction with an assrtment of activities from a variety of art disciplines, within a bigger framework. History of Jakarta Biennnale endeavors to hold activities and events are not merely held to enhance public appreaciation, but also make art as a part of public life AbstrakSecara historis dan kultural, Asia Tenggara merupakan tempat bertemunya peradaban besar dan agama-agama tertua yang berpengaruh melalui perdagangan , migrasi dan kolonialisasi. Sejarah seni di Asia Tenggara adalah bagian dari kebudayaan yang berangkat dari keseharian manusia, penyelengaraan kegiatan Jakarta Biennale mampu menunjukkan gemerlap kota Jakarta sebagai bagian dari proses berkesenian dan pengembangan kebudayaan secara umum. Terdapat dua perbedaan utama dari perkembangan Pameran Jakarta Biennale sebelumnya dengan pameran kali ini. Pertama, pameran Jakarta Biennale ibi bersifat internasional . Kedua, pameran ini telah mempertemukan sejumlah kegiatan dari berbagai disiplin seni menjadi satu kesatuan bingkai yang lebih besar. Sejarah kegiatan Pameran Jakarta Biennale tidak hanya untuk mendorong aktifitas apresiasi masyarakat terhadap seni semata, akan tetapi juga berusaha menjadi bagian dari kehidupan masyarakat itu sendiri.